Astragalus mongholicus powder, a traditional Chinese medicine formula ameliorate type 2 diabetes by regulating adipoinsular axis in diabetic mice - Siyuan Xu; Bixian Ye; Jinlei Li; Yonghui Dou; Yuying Yu; Yifan Feng; Lexun Wang; David Chi-Cheong Wan; Xianglu Rong (Frontiers in Pharmacology, 2022)
The global morbidity of obesity and type 2 diabetes mellitus (T2DM) has dramatically increased. Insulin resistance is the most important pathogenesis and therapeutic target of T2DM. The traditional Chinese medicine formula Astragalus mongholicus powder (APF), consists of Astragalus mongholicus Bunge [Fabaceae], Pueraria montana (Lour.) Merr. [Fabaceae], and Morus alba L. [Moraceae] has a long history to be used to treat diabetes in ancient China. This work aims to investigate the effects of APF on diabetic mice and its underlying mechanism. Diabetic mice were induced by High-fat-diet (HFD) and streptozotocin (STZ). The body weight of mice and their plasma levels of glucose, insulin, leptin and lipids were examined. Reverse transcription-polymerase chain reaction, histology, and Western blot analysis were performed to validate the effects of APF on diabetic mice and investigate the underlying mechanism. APF reduced hyperglycemia, hyperinsulinemia, and hyerleptinemia and attenuate the progression of obesity and non-alcoholic fatty liver disease (NAFLD). However, these effects disappeared in leptin deficient ob/ob diabetic mice and STZ-induced insulin deficient type 1 diabetic mice. Destruction of either these hormones would abolish the therapeutic effects of APF. In addition, APF inhibited the protein expression of PTP1B suppressing insulin–leptin sensitivity, the gluconeogenic gene PEPCK, and the adipogenic gene FAS. Therefore, insulin–leptin sensitivity was normalized, and the gluconeogenic and adipogenic genes were suppressed. In conclusion, APF attenuated obesity, NAFLD, and T2DM by regulating the balance of adipoinsular axis in STZ + HFD induced T2DM mice.